Optimization of Micro Hydro Power Plants to Support Community Energy and Indonesian National Army Training in Gunung Halu, West Bandung Regency - M. Syaiful Alim; Arya Dewa Nugroho; Suyono Thamrin; Rudy Laksmono4 (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Gunung Halu Village, Tangsi Jaya hamlet to reach 250 people in 2023, is faced with significant challenges related to the need for sustainable energy. The energy crisis and environmental issues have encouraged research into alternative energy sources, including Micro Hydro Power Plants (PLTMH), especially in areas with abundant water potential such as Gunung Halu, namely the Ciputri River. The main problem currently being faced is that the PLTMH, which was built in 2007 with a capacity of 18 kW has experienced overload due to population growth and increasing household electronic needs. The aim of the research is to determine the potential of PLTMH in Gunung Halu, develop ways to optimize PLTMH to provide the community's electricity needs and optimize PLTMH as an alternative option for TNI training areas. The method used in this research is a descriptive qualitative method which is carried out in depth so that it is supported by literature studies and then combined with field observation data, interviews and documentation. The research results show that the PLTMH that can be optimized on Gunung Halu is 30 kW by optimizing turbine efficiency and considering changes in height differences according to the characteristics of the area. In conclusion, it was found that optimizing the PLTMH is important to provide adequate electrical energy and support TNI training so that it hopes to become sustainable energy and a practical solution to increase local energy independence and support national defense.